The Igorot in the World Wide Web exploring the Igorot Ethnic Identity through the Communicative Act of Blogging - Rabia, Stephanie Luanne San Agustin; Lazaro, Patricio B. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2009)
The study entitled "The Igorot in the World Wide Web : exploring the Igorot Ethnic Identity through the Communicative Act of blogging" aimed toe determined how and why Igorot bloggers use their blogs as a means to actively represent themselves and assert their Igorot ethnic identities.
Thesis (M.A. Speech Communication)--University of the Philippines Diliman
Keywords: Igorots -- Social life and customs; Social media -- Philippines; Online social networks